2014
DOI: 10.1530/joe-14-0249
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose PTH increases osteoblast activity via decreased Mef2c/Sost in senescent osteopenic mice

Abstract: Intermittent administration of parathyroid hormone (PTH) 1-34 at a standard dose has been shown to induce anabolic effects in bone. However, whether low-dose PTH promotes bone formation during senescence is unknown. To address this issue, we determined the effects of low-dose PTH and analysed the underlying mechanisms in prematurely senescent mice that display osteopenia. Treatment of 9-week-old Samp6 mice for 6 weeks with PTH at a standard dose (100 mg/kg per day) increased vertebral and femoral bone mass and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…PTH(1-34), also known as Teriparatide, is an FDA-approved anabolic drug for osteoporosis, increasing bone deposition. It has also been demonstrated that, although PTH(1-34) can also stimulate bone resorption, the net effect of intermittent daily administration is the increase in bone mass (Hock & Gera, 1992;Burr et al 2001;Oswald et al 2014;Saidak et al 2014;Takao-Kawabata et al 2015). Under some conditions, PTH(1-34) can be used to improve fracture healing (Chiang et al 2013), although this may be dependent on the severity and location of bone injury as well as on an individual's overall bone health.…”
Section: Introductionmentioning
confidence: 99%
“…PTH(1-34), also known as Teriparatide, is an FDA-approved anabolic drug for osteoporosis, increasing bone deposition. It has also been demonstrated that, although PTH(1-34) can also stimulate bone resorption, the net effect of intermittent daily administration is the increase in bone mass (Hock & Gera, 1992;Burr et al 2001;Oswald et al 2014;Saidak et al 2014;Takao-Kawabata et al 2015). Under some conditions, PTH(1-34) can be used to improve fracture healing (Chiang et al 2013), although this may be dependent on the severity and location of bone injury as well as on an individual's overall bone health.…”
Section: Introductionmentioning
confidence: 99%
“…sion of sclerostin expression (3,4). Furthermore, recent studies revealed that PTH promoted bone anabolism by stimulating aerobic glycolysis in osteoblasts via insulinlike growth factor signaling (5).…”
mentioning
confidence: 99%
“…WISP1 can increase osteogenesis through bone morphogenetic protein 2 (BMP-2), and bone formation through parathyroid hormone treatment can progress through WISP1 expression (Saidak et al 2014). Bone formation following growth plate cartilage injury has been demonstrated to involve expression of the WISP1 gene.…”
Section: Wisp1 In Cellular Repair and Proliferationmentioning
confidence: 99%